(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
This cross sectional descriptive study was done by using nonprobability sampling technique and performed by examining 63 (sixty three) cerebellum. Out of them 40 postmortem human cerebellum collected from Bangladeshi cadavers of both sexes (male 25 and female 15) age ranging from 5 to 60 years and 23 cerebellums from caesarian section of intrauterine death cases of both sex (male 14 and female 9) age ranging from 34 wks to 41 wks. of gestation. Specimens were collected from dead bodies autopsied on different dates from April’ 2009 to September 2009 at the autopsy laboratory of department of Forensic Medicine and prenatal cases from Gynaecology and Obstetrics Department of Mymensingh Medical College, Mymensingh. The collected specimens were grouped into three age groups like Group A (28 to 42 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years) and, two sex groups (male and female). Volume of the cerebellum was measured by applying the principle of fluid displacement method (Brown et al 1986) with the help of a 1000 ml beaker and 1000 ml cylinder. After placing the cerebellum in the beaker, water was gradually added to it from a measuring cylinder which was previously filled with 500 ml of water and then the beaker was filled exactly up to 500 marking. The remaining portion of water in the cylinder, which indicates the amount of displaced fluid by the cerebellum, was exactly recorded and was expressed in milliliter (ml). The measurement was taken after fixation into 10% formol saline. The mean (SD) volume was in Group A 15.48±2.85 ml, B 117.74+15.01ml and C 108.60±15.59 ml respectively and it was also observed that the mean volume of the cerebellum increased with age upto certain level then slightly decreased in the late age Group C. The mean volume was maximum in Group B (117.74 ml) and was minimum in Group A (15.48 ml). The mean difference of the cerebellar volume between Groups A&B, A&C was statistically highly significant but differences between B&C was also statistically significant at p <0.05 level. J. Dhaka National Med. Coll. Hos. 2015; 21 (02):15-18